Environmental Damage Due to Hazardous and Toxic Pollution: A Case Study of Citarum River, West Java, Indonesia - Riyadi, Bambang Slamet; Alhamda, Syukra; Airlambang, Sutrysno; Anggreiny, Ratih; Anggara, Ariff Trisetia; Sudaryat (International Journal of Criminology and Sociology, 2022)
Until now, environmental crimes in the Citarum watershed, especially the disposal of hazardous and toxic waste (HTW) still occurs. Consequently, there are a countless number of disasters that are happening in a day. However, where is the social control of bureaucrats of the State Ministry for the Environment of the Republic of Indonesia? This research approach method was the qualitative method. The research results showed that the perpetrators of environmental damage to the Citarum watershed were not aware that the impact of environmental damage was more violent than other crimes. It was because this type of crime sometimes had unexpected impacts related to the intensity, duration, and extent of the area affected. Therefore, the efforts to prevent environmental crimes against the Citarum river water should cover various aspects. These include very strict supervision in terms of check and balance of the independent state institutions as well as the discretion given to the authorities in the disposal of hazardous and toxic waste into the Citarum River.